2020
DOI: 10.1111/1744-9987.13500
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new measurement method of indoxyl sulfate in hemodialysis patients

Abstract: Indoxyl sulfate (IS) is related to the development of cardiovascular disease and total mortality in dialysis patients. High‐performance liquid chromatography (HPLC) is the conventional measurement approach. However, the HPLC method is difficult to perform in real time. Recently, the IS Assay Kit “NIPRO”, which enables the measuring of total IS by the enzyme method, was developed. This new reagent allows the easy and quick measurement of many samples using the automatic biochemical analyzer. Moreover, it was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Additional plasma and serum samples were stored in a −80°C freezer for batched measurement of additional study factors by enzyme‐linked immunosorbent assays (ELISA), at the research laboratory within the Department of Nephrology at Monash Health. Samples were analysed as per the manufacturer's protocols for total, as opposed to free IS using the enzyme method (human kit supplied by Nipro Corporation, Osaka, Japan), as outlined in Abe et al 11 This study found the enzyme method for measuring total IS was accurate, repeatable and correlated well with HPLC measurements. Manufacturer's protocols were also applied for measurement of IL‐6 (AB46027, Abcam Australia), MDA‐LDL (10‐1143‐01, human oxidized LDL kit, Mercodia, Uppsala, Sweden) and α1M (Human Alpha‐1‐Microglobulin ELISA Kit AB22689 Abcam UK, for plasma; and Human alpha‐1 microglobulin ELISA Kit AB108884, Abcam UK, for dialysate).…”
Section: Methodsmentioning
confidence: 87%
“…Additional plasma and serum samples were stored in a −80°C freezer for batched measurement of additional study factors by enzyme‐linked immunosorbent assays (ELISA), at the research laboratory within the Department of Nephrology at Monash Health. Samples were analysed as per the manufacturer's protocols for total, as opposed to free IS using the enzyme method (human kit supplied by Nipro Corporation, Osaka, Japan), as outlined in Abe et al 11 This study found the enzyme method for measuring total IS was accurate, repeatable and correlated well with HPLC measurements. Manufacturer's protocols were also applied for measurement of IL‐6 (AB46027, Abcam Australia), MDA‐LDL (10‐1143‐01, human oxidized LDL kit, Mercodia, Uppsala, Sweden) and α1M (Human Alpha‐1‐Microglobulin ELISA Kit AB22689 Abcam UK, for plasma; and Human alpha‐1 microglobulin ELISA Kit AB108884, Abcam UK, for dialysate).…”
Section: Methodsmentioning
confidence: 87%
“…An enzymatic method was used to evaluate indoxyl sulfate concentrations in the current study. Although high-performance liquid chromatography is the gold standard, enzymatic methods have been reported to correlate well with high-performance liquid chromatography 14,15 . However, we could not exclude the influence of the indoxyl sulfate measurement method.…”
Section: Discussionmentioning
confidence: 99%
“…Indoxyl sulfate was measured using the enzyme method (NIPRO Corporation, Osaka, Japan) at the core laboratory of Okayama University, as previously described 14,15 . Briefly, sulfatase converted indoxyl sulfate to indoxyl.…”
Section: Measurement Of Indoxyl Sulfatementioning
confidence: 99%
“…Elevated IS levels in chronic kidney disease (CKD) are associated with hazardous effects like progression of CKD [3] cardiovascular disease (CVD) and all-cause mortality in HD patients [4].…”
Section: Introductionmentioning
confidence: 99%